Comparison of the Efficacy of Conventional Versus Sequential Regimen in Patients of Gastritis Presenting with Helicobacter Pylori - Ahmad Zaka Subhani, Israr-Ul-Haque, Ghias-Ul-Hassan, Muhammad Yasir Younis, Muhammad Asim Hameed, Ghias-Un-Nabi-Tayyab, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the efficacy of conventional versus sequential regimen in patients of gastritis presenting with Helicobacter pylori. Study Design: Randomized Controlled Trial Setting: Unit I, Department of Gastroenterology, Lahore General Hospital, Lahore Duration of Study: Six months after the approval of synopsis i.e. 30th November 2017 to 30th May 2018. Methodology: 232 patients fulfilled inclusion criteria were enrolled in the study. Patients were randomly divided in two equal groups. In group A, conventional triple treatment was given. In group B, sequential therapy was given. After 30 days, urea breath test was done. Reports were assessed and if there will be no bacterium, and then efficacy was labeled. All this information was recorded through proforma. Data analysis was done using SPSS version 21. Results: The mean age of patients was 38.63±13.11year in conventional group and 36.46±12.16years in sequential group. In conventional group, there were 88 (75.9%) male and 28 (24.1%) females. In sequential group, there were 74 (63.8%) male and 42 (36.2%) females. With conventional therapy, efficacy was achieved in 82 (70.7%) patients while with sequential therapy, efficacy was achieved in 100 (86.2%) patients. The difference was significant (p<0.05). Conclusion: Thus the sequential therapy is more effective than conventional therapy for eradication of H. pylori in patients of gastritis. Keywords: Gastritis, H. pylori, conventional therapy, sequential regimen